Does Corruption Increase Antidumping Investigations? - Avsar, Veysel; Habiyaremye, Alexis; Unal, Umut (International Journal of Economics and Financial Issues, 2016)
This paper represents the first attempt to examine the influence that corruption exerts on the worldwide use of antidumping (AD) claims as a means to seek trade protection. Since the inception of the World Trade Organization (WTO) and the concomitant dramatic fall in tariffs, antidumping duties have become one of the few permissible measures to provide temporary protection to foreign competition. Increased lobbying pressure in this area has gone hand in hand with the explosion of number of AD filings. We hypothesized that corruption gives the import competing sector the opportunity to more effectively lobby for trade protection and this can be expected to result in more attempts to use AD filings. Using cross-country data on AD investigations, we provide support to this hypothesis. Keywords: Antidumping, Corruption, Institutions, Trade Policy JEL Classifications: D72, D73, F13, F15